PENGEMBANGAN MEDIA PEMBELAJARAN WORDWALL BERBASIS TPR (TOTAL PHYSICAL RESPONSE) PADA PEMBELAJARAN BAHASA INGGRIS KELAS IV SEKOLAH DASAR - Dwi Maryani, Siska; Herlina; Yustia Suntari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop an interactive learning media called Wordwall based on the Total Physical Response (TPR) method for teaching English to fourth-grade elementary school students. The study was motivated by the limited use of digital and kinesthetic-based media in English learning, which often causes students to become passive and less engaged. The development model used was the 4D model by Thiagarajan, Semmel, and Semmel, consisting of four stages: Define, Design, Develop, and Disseminate. Data were collected through observation, interviews, questionnaires, and tests. Validation was conducted by three experts material, language, and media with an average validity score of 96.2%, categorized as very valid. Practicality tests involving one-to-one and small group evaluations obtained an average score of 95.9%, while the field test showed an N-Gain value of 0.86 or 86.5%, categorized as high effectiveness. The findings indicate that the Wordwall-based TPR media is valid, practical, and effective in improving students’ vocabulary mastery and learning engagement. This integration of digital and kinesthetic learning fosters active participation, enhances motivation, and creates an enjoyable learning atmosphere in English classes.